Treatment-Related Outcomes From Blunt Cerebrovascular Injuries: Importance of Routine Follow-Up Arteriography - Biffl, Walter L. (2002)
OBJECTIVE: To assess the impact of routine follow-up arteriography on the management and outcome of patients with acute blunt cerebrovascular injuries (BCVI). SUMMARY BACKGROUND DATA: During the past 5 years there has been increasing recognition of BCVI, but the management of these lesions remains controversial. The authors previously proposed a grading system for BCVI, with grade-specific management guidelines. The authors have noted that a significant number of injuries evolve within 7 to 10 days, warranting alterations in therapy. METHODS: A prospective database of a regional trauma center’s experience with BCVI has been maintained since 1990. A policy of arteriographic screening for BCVI based on injury mechanism (e.g., cervical hyperextension) and injury patterns (e.g., cervical and facial fractures) was instituted in 1996. A grading system was devised to develop management protocols: I = intimal irregularity; II = dissection/flap/thrombus; III = pseudoaneurysm; IV = occlusion; V = transection. RESULTS: From June 1990 to October 2001, 171 patients (115 male, age 36 ± 1 years) were diagnosed with BCVI. Mean injury severity score was 28 ± 1; associated injuries included brain (57%), spine (44%), chest (43%), and face (34%). Mechanism was motor vehicle crash in 50%, fall in 11%, pedestrian struck in 11%, and other in 29%. One hundred fourteen patients had 157 carotid artery injuries (43 bilateral), and 79 patients had 97 vertebral artery injuries (18 bilateral). The breakdown of injury grades was 137 grade I, 52 grade II, 32 grade III, 25 grade IV, and 8 grade V. One hundred fourteen (73%) carotid and 65 (67%) vertebral arteries were restudied with arteriography 7 to 10 days after the injury. Eight-two percent of grade IV and 93% of grade III injuries were unchanged. However, grade I and II lesions changed frequently. Fifty-seven percent of grade I and 8% of grade II injuries healed, allowing cessation of therapy, whereas 8% of grade I and 43% of grade II lesions progressed to pseudoaneurysm formation, prompting interventional treatment. There was no significant difference in healing or in progression of injuries whether treated with heparin or antiplatelet therapy or untreated. However, heparin may improve the neurologic outcome in patients with ischemic deficits and may prevent stroke in asymptomatic patients. CONCLUSIONS: Routine follow-up arteriography is warranted in patients with grade I and II BCVIs because most of these patients (61% in this series) will require a change in management. A prospective randomized trial will be necessary to identify the optimal treatment of BCVI.